THE IMPACT OF FARMER’S ATTITUDE AND PERCEIVED QUALITY TO FARMER’S SATISFACTION AND ITS EFFECT ON BRAND LOYALTY - Daniel Wahyudi; Eka Sulistiani; Muhammad Haris Muhajat (Journal of Research in Business, Economics, and Education, 2019)
This study aims to analyze the impact of farmers attitude and perceived quality to farmers satisfaction and its effect on brand loyalty in using Bisi-2 hybrid corn seeds in Tekasire village. This study uses causal analysis methods, thus multiple linear regression is utilized to analyze answer the research question. Before the data is analyzed, there will be some tests apply to the data, this procedure is called as classical assumption tests. The result revealed that perceived quality and customer attitude significantly and positively affect customer satisfaction of farmers toward Bisi-2 corn seed and so customer satisfaction affects brand loyalty, however direct relationship between perceived quality and brand loyalty is weak or not significant and so with relationship between customer attitude and brand loyalty. Bisi-2 corn seed sellers is suggested to pay attention on customer satisfaction as first priority since it is the only way to make their customers become loyal to their brand. Meanwhile customer satisfaction can be achieved by increasing customer positive attitude toward their product and perceived quality from customer point of view.